PENGARUH PERBANDINGAN JUMLAH TEPUNG KETAN DENGAN LIDAH BUAYA (Aloe Barbandesis Miller) TERHADAP KARAKTERISTIK DODOL LIDAH BUAYA - Ngurah Antawinarya, I Gusti; Subarjiati, Imacullata; Ngr. Agung, I Gst. (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 2 No 1 (2013): Jurnal ITEPA, 2013)
The aims of this research are to determine the effects of comparison between the amount of sticky rice flour with aloe on the characteristics of dodol and to find the right comparison between the amount of sticky rice flour and aloe to produce dodol with the best characteristics. The research design used is randomized group design with comparison between the amount of sticky rice flour and aloe respectively as follows: 100%: 0%, 85%:15%, 70%:30%, 55%:45%, and 40%:60%. The result was repeated three times producing 15 units of the experiment and the data was analyzed by variance analysis. If there was impact on the research, the analysis will be followed by Duncan’s test. The result of the research showed that comparison between the amount of sticky rice flour and aloe had significance effects on the content of water, dust, fat, protein, total sugar, antioxydant capacity, colour, aroma, taste, texture and overall acceptance. The best characteristics of dodol aloe was found on comparison between 40% sticky rice flour and 60% for aloe with the folowing criteria : water content 17,89%, ast content 0,53%, 11, 47%, fat content, protein content 7,34%, total sugar 45,80%, power antioxydant 50, 62%, texture elastic and overall acceptance is like. Keyword : sticky rice flour, aloe, dodol.
Keywords: dodol,rice flour,aloe